PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP N 1 SINTUK TOBOH GADANG - Syamsir, Yessi (Departemen Matematika, 2024)
The skill of understanding mathematical concepts is the most essential thing for students to master because it is the basis for achieving other abilities and learning objectives. However, the reality is that this skill is still fairly low at SMP N 1 Sintuk Toboh Gadang (Sintoga). As evidenced by the results of observations and initial tests, most students have not been able to solve problems correctly. Alternatives to improve these skills include through the implementation of the Numbered Head Together (NHT) type cooperative learning model. The focus of this research is to reveal and describe whether the implementation of the NHT model is better than direct learning. This study is a quasi-experimental research. The research instrument is a test. The t-test results showed that the P-value = 0.03 (α = 0.05) means reject H0. It is concluded that the implementation of the NHT model is better than direct learning in terms of concept understanding.Keywords– Understand Mathematical Concepts, NHT